Oriental splendor [videorecording] - Barrat, James; Iwata, Mary Ellen; Janse, Andre; Kaptijn, Ellen; Okkerse, Tom.; Schots, Frank; Schroevers, Martijn; Taylor, David; Verkerk, Mark. (Hilversum, The Netherlands produced for the Learning Channel, Discovery Communication by EMS Productions, 1995)
A concubine rose to become empress of all China, and squandered her nations destiny on her own private pleasure, at the Summer Palace of Beijing. From India's Red Fort, a Maghul emperor gazed upon the Taj Mahal - a movement to eternal love and a broken heart. At Thailand's Royal Palace of Bangkok, a woman named Anna tutored the future king of Siam, and a love monk held off the armies of Europe. This Asian journey ends at an entire city of Palaces built on the summit of a volcano, India's Jodhpur.
The Summer Palace (Beijing, China) -- The Red Fort and the Taj Mahal (India) -- The Grand Palace (Bangkok, Thailand).
VHS.
Credits : Narrator, John Nolan.
Keywords: The Summer Palace (Beijing, China).; Palaces -- China -- Beijing; Palaces -- India; Palaces -- Thailand -- Bangkok; Taj Mahal (India).; The Grand Palace (Bangkok, Thailand).; The Red Ford (India).